Liposomal Bupivacaine Utilization in Total Knee Replacement Does Not Decrease Length of Hospital Stay - Schumer, Grace; Mann, John W., III; Stover, Matthew David; Sloboda, John F.; Cdebaca, Carol Sue; Woods, Gina Moss (The Journal of Knee Surgery, 2019)
Liposomal bupivacaine has reportedly been used as an adjunct for perioperative pain management in total knee replacement (TKR). The purpose of our single-blind, prospective study is to show that wound infiltration with long-acting liposomal bupivacaine during TKR will shorten length of stay (LOS) as compared with standard bupivacaine injection and spinal anesthetic with or without spinal narcotic. A total of 195 patients were randomized into three groups: wound infiltration with bupivacaine and a spinal with narcotic (Group 1, N = 65), wound infiltration with liposomal bupivacaine and a spinal without narcotic (Group 2, N = 67), and bupivacaine wound infiltration with a spinal without narcotic (Group 3, N = 64). The groups were then compared with look for any benefit in using the liposomal bupivacaine with regard to LOS, pain control, function, and complications. There was a trend toward a decreased LOS (days) in the liposomal bupivacaine (Group 2) with a mean LOS of 1.83 as compared with wound infiltration with bupivacaine with spinal narcotic LOS of 2.04 (Group 1) and without spinal narcotic LOS of 1.94 (Group 3). These results were not statistically significant (p = 0.37). Patient-reported pain scores were no different between the three groups. The daily narcotic usage (morphine equivalents) during the hospitalization was statistically highest in the liposomal bupivacaine group at 77.2 versus 55.0 in Group 1 and 68.1 in Group 3 (p = 0.025). Nausea or vomiting was most common in Group 1 at 42%, followed by 28% in Group 2 and 22% in Group 3. Pruritus was most common in the spinal narcotic group at 38% versus Group 2 at 14% and Group 3 at 11%.Liposomal bupivacaine showed a trend toward a decreased LOS, but this was not statistically significant. There was no difference in pain scores reported by these patients. In conclusion, we cannot justify the extra cost of liposomal bupivacaine as compared with plain bupivacaine as an adjunct for perioperative pain management in TKR patients.
Keywords: liposomal bupivacaine; pain management total knee replacement; intra-articular injection total knee replacement